История России с древнейших времен - Соловьев Сергей Михайлович (1991)
Экземпляры: КХ (20100421) / Инвентарный номер: 995237 / Цена: 19.20 / Сис.шифр: 63.3(2)1 / Авт.знак: С 60 / ГРНТИ: 03 / ББК: 63.3(2)